Witnessing violence in early secondary school predicts subsequent student impairment. Issue 12 (16th September 2018) - Janosz, Michel; Brière, Frédéric N; Galand, Benoît; Pascal, Sophie; Archambault, Isabelle; Brault, Marie-Christine; Moltrecht, Brigitte; Pagani, Linda S
Abstract : Background: Past research suggests that adolescents who witness violence are at risk of adjustment problems. However, few studies have implemented a longitudinal design and have accounted for direct experiences of victimisation and other major confounders. This prospective study examines the relationship between witnessing school violence and subsequent impairment and whether such associations depend on the kind of violence witnessed. Methods: 3936 adolescents from Quebec (Canada) were followed from ages 12 through 15 years. Linear regression tested associations between witnessing school violence at age 13 and subsequent antisocial behaviour (drug use, delinquency), emotional distress (social anxiety, depressive symptoms) and academic adjustment (school achievement, engagement) at age 15. We compared the relative contribution of differing forms of witnessing school violence versus being victimised directly. Results: General school violence predicted later impairment. The adjusted associations between indirectly experiencing violence as a bystander and subsequent impairment were comparable to those of direct victimisation. Witnessing covert and major violence was associated with drug use and delinquency. Witnessing minor violence was associated with increases in drug use, social anxiety, depressive symptoms and decreases in school engagement. Conclusions: Almost all students witnessed school violence, which predicted impairment. Witnessing violence was associated with risk of subsequent adjustment problems 2 years later. Directly experienced victimisation showed a comparable magnitude of risk. This suggests that when it comes to symptoms of conduct disorder, witnessing violence might have the same impact as experiencing it directly. Witnessing earlier covert and major violence predicted social impairment whereas minor violence predicted psychological and academic impairment.